Schumpeterian entrepreneurship in Europe compared to other industrialized regions - Magnus Henrekson; Tino Sanandaji (Research Institute of Industrial Economics (IFN), 2017)
We examine whether Europe has an "entrepreneurship deficit" compared to other industrialized regions. Cross-country comparisons are difficult due to the lack of standard empirical definitions of entrepreneurship. Measures focusing on small business activity and startup rates suggest that Europe has the same or higher rates of entrepreneurship than the U.S. and East Asia. However, most business activity is not entrepreneurial in the Schumpeterian sense. We rely on empirical measures that more closely tally Schumpeterian entrepreneurship. These include top global firms founded in recent decades, highly valued unicorn startups, venture capital investments as a share of GDP, and the number of self-made dollar billionaires per capita who earned their wealth by creating new firms. Western Europe is shown to underperform in all four measures of high-impact Schumpeterian entrepreneurship relative to the U.S. Once we account for Europe's strong performance in technological innovation, an "entrepreneurship deficit" relative to China and East Asia becomes apparent. This underperformance is missed by most standard measures, but captured by the GEM measure Growth Expectation early-stage Entrepreneurial Activity. China is found to perform surprisingly well in Schumpeterian entrepreneurship, especially compared to Eastern Europe.
Keywords: L5; M13; O31; P14; 330; Billionaire entrepreneurs; Entrepreneurship; Innovation; Institutions; Regulation; Self-employment